Chronic recurrent vomiting associated with primary gastric volvulus in infant: A case report and review of literature - Maheshkumar Manilal Vaghela; Amit Kumar Sinha; Bindey Kumar; Prem Kumar (Wolters Kluwer Medknow Publications, 2017)
Gastric volvulus is an uncommon entity found in the paediatric population. We are reporting a case of chronic gastric volvulus presented to us with the complaints of recurrent vomiting after each feed. The vomiting was projectile, nonbilious, and the content was milk. The patient was evaluated by clinical and radiological means in the form of the X-ray abdomen, ultrasound abdomen, upper gastrointestinal (GI) contrast study, and computed tomography scan of the abdomen. The upper GI contrast study was suggestive of gastric volvulus. The patient was operated and gastropexy was done. There was lax gastrocolic ligament with increased distance between stomach and transverse colon without any obvious gastric volvulus. Postsurgery, the patient was symptom-free.